Spatial and temporal expression of immunoglobulin superfamily member 1 in the rat - Joustra, Sjoerd D; Meijer, Onno C; Heinen, Charlotte A; Mol, Isabel M; Laghmani, El Houari; Sengers, Rozemarijn M A; Carreno, Gabriela; van Trotsenburg, A S Paul; Biermasz, Nienke R; Bernard, Daniel J; Wit, Jan M; Oostdijk, Wilma; et al. (Journal of endocrinology, 2015)
Loss-of-function mutations in the immunoglobulin superfamily member 1 (IGSF1) gene cause an X-linked syndrome of central hypothyroidism, macroorchidism, variable prolactin and GH deficiency, delayed pubertal testosterone rise, and obesity. To understand the pathophysiology of this syndrome, knowledge on IGSF1's place in normal development is imperative. Therefore, we investigated spatial and temporal protein and mRNA expression of IGSF1 in rats using immunohistochemistry, real-time quantitative PCR (qPCR), and in situ hybridization. We observed high levels of IGSF1 expression in the brain, specifically the embryonic and adult choroid plexus and hypothalamus (principally in glial cells), and in the pituitary gland (PIT1-lineage of GH, TSH, and PRL-producing cells). IGSF1 is also expressed in the embryonic and adult zona glomerulosa of the adrenal gland, islets of Langerhans of the pancreas, and costameres of the heart and skeletal muscle. IGSF1 is highly expressed in fetal liver, but is absent shortly after birth. In the adult testis, IGSF1 is present in Sertoli cells (epithelial stages XIII–VI), and elongating spermatids (stages X–XII). Specificity of protein expression was corroborated with Igsf1 mRNA expression in all tissues. The expression patterns of IGSF1 in the pituitary gland and testis are consistent with the pituitary hormone deficiencies and macroorchidism observed in patients with IGSF1 deficiency. The expression in the brain, adrenal gland, pancreas, liver, and muscle suggest IGSF1's function in endocrine physiology might be more extensive than previously considered.